Politik Hukum Regulasi Hukum Ekonomi Syar’iah pada Lembaga Keuangan Syari’ah di Indonesia - Zeehan Fuad Attamimi; Ali Ismail Shaleh (Jurnal Hukum Ekonomi Islam, 2018)
Sharia financial institutions are institutions that play a role in carrying out business activities in the financial sector based on sharia principles. Islamic financial institutions as a financial institution have a different financial system from conventional financial institutions. The Islamic financial institution system has a system function as a financial intermediary between people who have funds to provide people who need funds so that the Islamic financial system uses a profit sharing system. The profit sharing system for Islamic financial institutions does not recognize interest which is commonly called usury. In carrying out their duties and functions, Islamic financial institutions need sharia economic law which is regulated in the regulatory framework of sharia economic law. the regulatory framework for shari'ah economic law is made in the sharia economic law politics carried out by the government. So, how is the regulation of Islamic financial institutions which are political products of sharia economic law made by the government according to or not in accordance with the principles and objectives of sharia in accordance with the Al-Quran and hadith. The purpose of this study is to determine the development of sharia economic law regulations in making legal political products contained in Sharia Financial Institutions and to become recommendations for strengthening the political law and sharia economic regulation in Indonesia. This study uses a normative juridical method, namely research that refers to statutory regulations, research results, journals, data and other references, which are analyzed using a qualitative descriptive method. The results showed that there are still practice inconsistencies in Islamic financial institutions that are not in accordance with the fatwa of the National Sharia Council or are not in accordance with sharia and need to be addressed through the regulation of Islamic financial institutions, which are sharia law products produced through political law by authorized institutions. The government in the process of positifying sharia economic regulations in Indonesia should shape the direction, methods, and policies in formalizing laws related to the sharia economy in Indonesia. The political role of law is carried out by the government through creating regulations as checks and balances in making policies that can support sharia economic activity and economic growth. Keywords: Islamic financial institutions, sharia economic law, political law. Abstrak Lembaga keuangan syariah merupakan suatu lembaga yang berperan melakukan kegiatan usaha dalam bidang keuangan dengan berdasarkan pada prinsip-prinsip syari’ah. Lembaga keuangan syariah sebagai suatu lembaga keuangan memiliki sistem keuangan yang berbeda dengan lembaga keuangan konvensional. Sistem lembaga keuangan syariah memiliki fungsi sistem sebagai perantara keuangan antara orang yang memiliki dana untuk memberikan orang yang membutuhkan dana sehingga sistem keuangan syariah menggunakan sistem bagi hasil. Sistem bagi hasil lembaga keuangan syariah tidak mengenal bunga yang biasa disebut riba. Lembaga keuangan syariah dalam menjalankan tugas dan fungsi perlu hukum ekonomi syari’ah yang diatur dalam kerangka regulasi hukum ekonomi syari’ah. kerangka regulasi hukum ekonomi syari’ah dibuat dalam politik hukum ekonomi syariah yang dilakukan oleh pemerintah. Sehingga, bagaimana regulasi lembaga keuangan syariah yang merupakan produk politik hukum ekonomi syariah yang dibuat oleh pemerintah sesuai atau tidak sesuai menjalankan prinsip-prinsip dan tujuan syariah sesuai dengan Al-quran dan hadits. Tujuan dari penelitian ini adalah untuk mengetahui perkembangan regulasi hukum ekonomi syariah dalam membuat produk politik hukum yang terdapat pada Lembaga Keuangan Syari’ah serta menjadi rekomendasi untuk penguatan politik hukum dan regulasi ekonomi syariah di Indonesia. Penelitian ini menggunakan metode yuridis normatif, yaitu penelitian yang mengacu pada peraturan perundang-undangan, hasil penelitian, jurnal, data dan referensi lainnya, yang dianalisis dengan metode deskriptif kualitatif. Hasil penelitian menunjukkan Masih terdapat ketidaksesuaian praktik dalam Lembaga keuangan syariah yang tidak sesuai fatwa Dewan Syariah Nasional atau tidak sesuai syariah dan perlu untuk dibenahi melalui regulasi Lembaga keuangan syariah yang merupakan produk hukum syariah yang dihasilkan melalui politik hukum oleh lembaga berwenang. Pemerintah dalam proses positifikasi regulasi ekonomi syariah di Indonesia sepatutnya membentuk arah, cara, serta kebijakan dalam memformalkan hukum-hukum yang berkaitan dengan ekonomi syariah di Indonesia. Peran politik hukum yang dilakukan oleh pemerintah melalui menciptakan regulasi sebagai checks and balances dalam membuat kebijakan-kebijakan yang dapat mendukung kegiatan ekonomi dan pertumbuhan ekonomi syariah.. Keywords: Lembaga Keuangan Syariah, hukum ekonomi syariah, Politik hukum.